Green Port Industry to Support the Offshore Wind Sector: A Proposal Framework - Monalisa Godeiro; Mario González; Dylan Jones; Negar Akbari; Gabriela Nascimento; David Melo; Rafael Vasconcelos; Andressa Santiso; Luana Nogueira; Mariana Almeida; José Toledo (Energies)
In recent years, offshore wind power has become increasingly relevant as a key alternative for contributing to the global economy’s decarbonization. Also, the accelerated technological development of the offshore wind turbine influences the increase in size and weight of its main components. This requires an appropriate port infrastructure to support the installation, operation, and maintenance and future decommissioning of offshore wind farms, and especially to serve as an area for manufacturing these components, addressing logistical challenges associated with land transport. This research aims to identify the factors that characterize a suitable port to support the offshore wind industry, also bringing the new green port industry concept. A systematic literature review was conducted via analyses of 126 documents, and a survey procedure was applied to validate the proposed model. As a result, a characterization model was proposed that includes 71 factors classified into 6 dimensions: physical characteristics, port layout, connectivity, port operation, port–farm performance optimization, and governance for sustainability, which is the main novelty of this study. The results contribute to the advancement of the offshore wind energy sector and can provide significant benefits for regional development and local communities with offshore wind potential.